Analisis Kinerja Keuangan Dengan Menggunakan Rasio Likuiditas, Solvabilitas, Dan Probabilitas Pada Bank Maluku- Malut - Amylia Sisin; Wanda Wanda; Aisun Warhangan; Syaiful Pakay (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This journal aims to analyze the financial performance of Bank Maluku-Malut using the ratio of liquidity, solvency and profitability. This research was conducted to understand the stability and ability of a bank to face financial risks and the potential profits generated. The annual financial data of Bank Maluku-Malut for the last five years is used as the research sample